Effects of non-surgical factors on digital replantation survival rate: a meta-analysis - Zhichao Ma; Feng Guo; Jun Qi; Wenpei Xiang; J. Zhang (2015)
This study aimed to evaluate the risk factors affecting survival rate of digital replantation by a meta-analysis. A computer retrieval of MEDLINE, OVID, EMBASE, and CNKI databases was conducted to identify citations for digital replantation with digit or finger or thumb or digital or fingertip and replantation as keywords. RevMan 5.2 software was used to calculate the pooled odds ratios. In total, there were 4678 amputated digits in 2641 patients. Gender and ischemia time had no significant influence on the survival rate of amputation replantation ( P > 0.05). Age, injured hand, injury type, zone, and the method of preservation the amputated digit significantly influence the survival rate of digital replantation ( P < 0.05). Children, right hand, crush, or avulsion and little finger are the risk factors that adversely affect the outcome. The level of evidence: Level 5*.